Turkey's globalizing economy - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The end of the Cold War has been a catalyst for Turkish economic relations with its neighbors. Turkey moved from the periphery to the center of a region that is transforming politically, socially and economically very fast. It is now surrounded by 13 sovereign nation states, which are more or less open to international trade and factor movements. All these new nation states have become potential partners for all kinds of economic activities. Due to their proximity, they are easily accessible markets for Turkish exports of goods or for imports of energy. Furthermore, they could provide the Turkish economy with cheap labor force - either as migrants to Turkey or as workers for Turkish plants to be established in the neighborhood.
Keywords: 330